2013
DOI: 10.1128/jvi.01242-13
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E4orf4 Protein-Induced Death of p53 −/− H1299 Human Cancer Cells Follows a G 1 Arrest of both Tetraploid and Diploid Cells due to a Failure To Initiate DNA Synthesis

Abstract: The adenovirus E4orf4 protein selectively kills human cancer cells independently of p53 and thus represents a potentially promising tool for the development of novel antitumor therapies. Previous studies suggested that E4orf4 induces an arrest or a delay in mitosis and that both this effect and subsequent cell death rely largely on an interaction with the B55 regulatory subunit of protein phosphatase 2A. In the present report, we show that the death of human H1299 lung carcinoma cells induced by expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…We showed previously that E4orf4-expressing tumor cells with both 2n and 4n DNA content are arrested in G 1 and die (8). This arrest in G 1 seems due to an inability to initiate new rounds of DNA synthesis (8).…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…We showed previously that E4orf4-expressing tumor cells with both 2n and 4n DNA content are arrested in G 1 and die (8). This arrest in G 1 seems due to an inability to initiate new rounds of DNA synthesis (8).…”
mentioning
confidence: 90%
“…We showed previously that E4orf4-expressing tumor cells with both 2n and 4n DNA content are arrested in G 1 and die (8). This arrest in G 1 seems due to an inability to initiate new rounds of DNA synthesis (8). E4orf4's effects require an interaction with the B55 class of protein phosphatase 2A regulatory subunits (9,(14)(15)(16)(17), and we have found that at high levels, E4orf4 inhibits PP2A B55 (18) to induce effects on anaphase-promoting complex (APC) and perhaps other processes that may disrupt normal passage through mitosis (18,19).…”
mentioning
confidence: 94%
See 3 more Smart Citations